IRIS MURDOCH’S MORAL VISION IN UNDER THE NET - Seraj Uddin Pandith (Galaxy International Interdisciplinary Research Journal, 2021)
Iris Murdoch is one of the prominent mid-twentieth century novelists as well as a notable philosopher. In her works and novels what she sought was to illustrate a personal vision of man’s morality. This paper tries to show how Iris Murdoch’s novel reflects her moral vision. It is shown that her novel is not mere exemplification of her ideas expressed in her philosophical books. And, in her novels she depicted real characters in real society. For her, man’s capacity to love and to phantasies is a saving grace. This love is born out of caring for and ‘attention to others’, a phrase that Murdoch borrowed from Simone Weil. Murdoch’s novels as she has described are pilgrimage from illusion towards reality and also pointed out that ‘reality ‘as such is never arrived at in the books, any more than it is in life. She believes that morality is connected with change and progress. The study of this novel shows how Jake does his pilgrimage and sees true goodness through gradual apprehension of goodness in his surroundings.